Viridians group streptococci in patients undergoing tooth extraction - Dhotre, Shree V.; Dharne, Mahesh S.; Potdar, S.; Suklikar, J.; Suryawanshi, Namdev; Nagoba, Basavraj (European Journal of General Medicine, 2015)
The aerobic microflora of the oral cavity consists of viridians group of streptococci (VGS). The present study was carried out with an objective to evaluate the prevalence of VGS in patients undergoing tooth extraction and to study their antibiotic susceptibility pattern. Samples of subgingival dental plaques for microbiological studies were collected from 80 patients undergoing tooth extraction. The isolated streptococci were identified along with their antibacterial susceptibilities by automated Vitek 2 (bioMérieux) system in accordance with CLSI standards. A total of 260 VGS strains belonging to 05 phenotypic groups, namely mutans, salivarius, anginosus, sanguinus and mitis groups; along with few strains of Granulicatella like G. adiacens and G. elegans. Altogether a total of 15 species were isolated from the subgingival plaque of 80 patients undergoing tooth extraction. Among the 15 antibiotics tested, highest resistance was observed to lincosamides (36.2%) followed by macrolides (29.7%), tetracyclines (17.7%), cephems (15.1%), fluoroquinolones (14.4%), oxazolidinones (13.5%), streptogramins (12.7 %) and penicillins (7.9%). However, all the 260 VGS strains were found susceptible to vancomycin and linezolid. In the subgingival plaque of patients undergoing tooth extraction, approximately 70% of streptococci belonged to three VGS groups, i.e. mitis, sanguinis and mutans groups. Streptococci of salivarus and anginosus groups were isolated sporadically (5%). Highest resistance was observed to lincosamides and macrolides (29.7%). Multiple antibiotic resistance was observed in mitis and salivarius group.